2020
DOI: 10.1080/23311908.2020.1823616
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cancer education on the practice of breast self-examination among adult women in Nigeria

Abstract: An evaluation of the use of cancer education on the practice of breast self-examination among adult women. The study utilized 90 adult women, their ages ranged from 30 to 50 years of age, with mean age of 38.33. The paticipants were randomly assigned to three groups: experimental group I (EGI), exeprimental group II (EGII) and the control group. The study utilized a 10-item index test of the practice of breast self-examination which was subjected to inter-rater face validity. Paired sample T-test was used to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
3
0
3
Order By: Relevance
“…Seluruh responden dalam penelitian ini berjenis kelamin perempun. Sebagian besar 62% berada di usia dewasa akhir (36)(37)(38)(39)(40)(41)(42)(43)(44)(45) Payudara sebagai salah satu pusat sensitivitas perempuan memiliki ribuan saraf. Sentuhan pada payudara memberikan sensasi tertentu yang membuat perempuan malu untuk menyentuhnya.…”
Section: Hasil Penelitianunclassified
“…Seluruh responden dalam penelitian ini berjenis kelamin perempun. Sebagian besar 62% berada di usia dewasa akhir (36)(37)(38)(39)(40)(41)(42)(43)(44)(45) Payudara sebagai salah satu pusat sensitivitas perempuan memiliki ribuan saraf. Sentuhan pada payudara memberikan sensasi tertentu yang membuat perempuan malu untuk menyentuhnya.…”
Section: Hasil Penelitianunclassified
“…Setelah mengikuti edukasi ini, para peserta mendapatkan pemahaman yang baik dan benar tentang kesehatan reproduksi khususnya terkait tindakan periksa payudara sendiri. Faktor utama yang meningkatkan risiko kanker payudara pada wanita termasuk kurangnya praktik pemeriksaan payudara sendiri (Udeze et al, 2020). Pemahaman yang baik tentang sesuatu hal dapat berdampak pada peningkatan kualitas hidup.…”
Section: Gambar 2 Pelaksanaan Posttestunclassified
“…BSE is singly assumed to be the most appropriate and effective strategy of ensuring early detection of breast cancer and could detect 40% of breast lesions among women if properly administered. Udeze et al (2020) also averred that Jenkins in his study explained that wherever breast self-examination is adequately practised, about seventy to eighty (70-80) percent of breast cancer are discovered by women themselves. Having good knowledge of breast self-examination and positive attitude towards it will have a great impact on the level of practice (Olajide et al, 2021) and this will go a long way in detecting breast cancer which had widely spread among women.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Breast cancer, according to Choumessi et al (2021), is considered the second most identified cancer among the whole world population and the commonest malignancy among women. Sadoh et al (2021) described breast cancer to be the commonest cancer in women and Udeze et al (2020) averred that it has become a problem all around the world; it accounted for 14% globally. Sharma (2021) reported that breast cancer accounted for 29.5% of all cancers in Africa and 33.3% annually in Nigeria, according to Ibitoye and Thupayegale-Tshwenegae (2019).…”
Section: Introduction Backgroundmentioning
confidence: 99%
See 1 more Smart Citation